Prospective memory deficits in subjects with schizophrenia spectrum disorders: A comparison study with schizophrenic subjects, psychometrically defined schizotypal subjects, and healthy controls - Wang, Ya; Chan, Raymond C.K.; Xin Yu; Shi, Chuan; Cui, Jifang; Deng, Yongyu (Schizophrenia research, 2008)
Memory impairment is one of the core deficits in schizophrenia. This study explored the memory profiles of schizophrenic and psychometrically defined schizotypal subjects. The study participants included 15 patients with schizophrenia, 41 schizotypal subjects, and 20 healthy controls. All of the participants completed verbal and visual memory, working memory, and prospective memory tasks. The results showed that patients with schizophrenia were impaired in all aspects of memory function, whereas the schizotypal subjects tended to show moderate to large impairment effect sizes in prospective memory. It is suggested that prospective memory be considered a potential endophenotype of schizophrenia.